Le Contrôle des Prix de transfert par les Administrations Fiscales des États de l'Afrique de l'Ouest - Diallo, Mamadou Dian (Université Côte d'Azur, 2025)
Les prix de transfert sont les prix auxquels une entreprise transfère des biens corporels, des actifs incorporels ou rend des services à des entreprises associées situées dans différents pays. En Afrique de l'Ouest, la question des prix de transfert est devenue un enjeu majeur pour les autorités fiscales, dès lors que ces pratiques peuvent être utilisées pour transférer artificiellement des bénéfices vers des juridictions à faible fiscalité, réduisant ainsi les recettes fiscales locales. Les pays de l'Afrique de l'Ouest connaissent une forte présence d'entreprises multinationales, en particulier, dans les secteurs des mines, du pétrole, des télécommunications etc. La faiblesse des capacités de contrôle fiscal, combinée à la complexité des montages fiscaux, rendent difficile la lutte contre l'érosion de la base d'imposition et le transfert de bénéfices à l'étranger.L'imposition des entreprises multinationales est gouvernée par les principes dits, de « territorialité » et de « pleine concurrence ». Il résulte des standards internationaux, que chaque entité d'un groupe multinational doit s'acquitter de l'impôt dans son pays d'implantation, en déterminant son bénéfice local comme si ses transactions avec les autres entités qui lui sont liées étaient effectuées avec des entreprises indépendantes.La présente thèse a pour objectif de traiter du contrôle des prix de transfert par les autorités fiscales des pays de l'Afrique de l'Ouest, dans un contexte où la lutte contre l'évasion fiscale internationale est devenue un enjeu mondial. A cet égard, le projet BEPS initié en 2013 par le G20 a formulé des recommandations à l'endroit des autorités fiscales permettant de traiter efficacement les questions liées aux pratiques BEPS. Ce projet a été intégré dans les principes de l'OCDE applicables en matière de prix de transfert à l'intention des entreprises multinationales et des administrations fiscales, renforcé par le Manuel Pratique de l'ONU sur les prix de transfert à l'intention des pays en voie de développement. Il replace le principe de pleine concurrence au centre de la lutte contre les pratiques BEPS. Transfer pricing refers to the price at which a company transfers tangible or intangible assets, or provides services to associated companies located in different countries. In West Africa, the issue of transfer pricing has become a major challenge for tax authorities, as these practices can be used to artificially shift profits to low-tax jurisdictions, thereby reducing local tax revenues. West African countries have a strong presence of multinational companies, particularly in the mining, oil, and telecommunications sectors. Weak tax audit capacities, combined with the complexity of tax arrangements, make it difficult to combat base erosion and profit shifting abroad.The taxation of multinational companies is governed by the so-called ''territoriality'' and ''arm's length'' principles. International standards stipulate that each entity within a multinational group must pay tax in its country of establishment, determining its local profit as if its transactions with other related entities were conducted with independent companies.This thesis aims to address transfer pricing controls by tax authorities in West African countries, in a context where the fight against international tax evasion has become a global issue. In this regard, the BEPS project initiated in 2013 by the G20 has formulated recommendations for tax authorities to effectively address issues related to BEPS practices. This project was incorporated into the OECD Transfer Pricing Guidelines for Multinational Enterprises and Tax Administrations, reinforced by the UN Practical Handbook on Transfer Pricing for Developing Countries. It places the arm's length principle at the center of the fight against BEPS practices.
Keywords: Administration fiscale; Afrique de l'Ouest; Afrique occidentale; Arm's length principle; BEPS; Base d’imposition; Control; Contrôle; Entreprises multinationales; Indirect profit shifting; Multinational enterprises; Pricing; Principe de pleine concurrence; Prix; Prix de cession interne; Prix de transfert (manipulation); Procédures fiscales; Tax authorities; Transfer; Transfer pricing; Transfert; Transfert indirect de bénéfices; West Africa

L'abus de droit en matière fiscale - Silberman, Lauren (Université Paris 12, 2025)
La théorie de l’abus de droit se présente comme un correctif essentiel à l’exercice des droits et un outil pour rétablir l’équilibre entre les intérêts en présence qui sont, en matière fiscale, ceux des contribuables, de l’administration fiscale et de la collectivité. L’abus de droit dépend du droit auquel une limite est apportée, limite pouvant être fixée par le législateur et selon une politique déterminée. Le législateur français a autonomisé la notion d’abus de droit en matière fiscale par la création d’une procédure spéciale de rectification assortie d’une majoration automatique punitive. La multiplication des dispositifs anti-abus d’assiette, qui s’applique dans le cadre de la procédure de rectification de droit commun, et qui n’entrainent pas l’application automatique d’une pénalité, a mené à une évolution de la notion d’abus de droit en matière fiscale. Ces dispositifs encadrent l’exercice de la liberté de choisir la voie la moins imposée, et se distinguent par leur régime et leur sanction. Corrélativement, l’Union européenne a développé sa propre notion d’abus de droit en matière fiscale, d’abord pour apprécier la compatibilité des dispositifs nationaux au droit primaire de l’Union, puis pour encadrer l’exercice des avantages offerts par le droit dérivé. Elle a ainsi dégagé une définition de l’abus de droit dont les critères diffèrent selon le droit abusé. L’OCDE s’est également intéressée à la notion d’abus en matière fiscale dans le cadre de la lutte contre l’érosion de la base d’imposition et le transfert de bénéfices. Son approche, plus pragmatique, se concentre sur les comportements des contribuables et de redevables qui doit être conforme non pas à la législation, mais à la politique fiscale et à l’équité fiscale entre les Etats et les opérateurs sur le marché mondial. L’Union européenne a adopté la même conception de l’abus de droit en matière fiscale par l’adoption d’un paquet de mesures de lutte contre la fraude et l’évasion fiscales. L’approche comportementale et économique de l’abus de droit coexiste aujourd’hui avec l’approche stricte et répressive du droit fiscal français. Cette coexistence a mené à la multiplication des dispositifs anti-abus d’assiette qui font entrer dans le champ de l’abus des comportements identifiés comme abusifs parce que non conformes à la conception internationale et européenne de l’équité fiscale. La notion de fictivité s’est élargie au profit de la notion de validité pour faire entrer dans son champ des comportements autrefois considérés comme de l’optimisation fiscale. Cette nouvelle approche de l’abus de droit en matière fiscale est source d’incertitudes pour les contribuables et les redevables et permet de s’interroger sur l’étendue de la notion d’abus de droit en matière fiscale. The theory of abuse of rights is an essential corrective to the exercise of rights, and a tool for restoring the balance between the interests involved, which, in tax matters, are those of the taxpayer, the tax authorities and the community. Abuse of rights depends on the law to which a limit has been set, a limit that can be set by the legislator according to a specific policy. The French legislator has given autonomy to the notion of abuse of rights in tax matters. It has created a provision to penalize abuse of rights, with a special rectification procedure and an automatic punitive surcharge. But it has also created anti-abuse provisions which apply within the framework of the ordinary rectification procedure and which do not entail the automatic application of a penalty. While all of these measures provide a framework for exercising the freedom to choose the path of least resistance to taxation, they differ in terms of their regimes and penalties. The European Union has also developed its own concept of abuse of rights in tax matters, firstly to assess the compatibility of national provisions with EU primary law, and then to provide a framework for the exercise of the advantages offered by secondary legislation. It has thus established a definition of abuse of rights, the criteria for which differ according to the law being abused. The OECD has also turned its attention to the notion of tax abuse as part of the fight against tax base erosion and profit shifting. Its more pragmatic approach focuses on the behavior of taxpayers and liables, which must be consistent not with legislation, but with tax policy and tax fairness between countries and operators on the global market. The European Union has adopted the same concept of abuse of rights in tax matters, with the adoption of a package of measures to combat tax fraud and evasion. Today, the behavioral and economic approach to abuse of rights coexists with the strict and repressive approach of French tax law. This coexistence has led to a proliferation of anti-abuse provisions that bring into the scope of abuse behaviors identified as abusive because they do not conform to international and European concepts of tax fairness. The notion of fictitiousness has been broadened in favor of the notion of validity, bringing within its scope behaviors previously considered as tax planning. This new approach to abuse of rights in tax matters is a source of uncertainty for taxpayers and liables and raises questions about the scope of the notion of abuse of rights in tax matters.
Keywords: Abus de droit; Abuse of rights; Anti-Abuse mesures; Choice of the path of least taxation; Choix de la voie la moins imposée; Dispositifs anti-Abus; Droit fiscal; Fraude et évasion fiscales; Fraude fiscale; Freedom of movement; Liberté de circulation; Optimisation fiscale; Tax fraud and evasion; Tax planning

La monnaie électronique dans les espaces bancaires européens, sous régionaux africains et OHADA - Fougou, Pierre Damien (Université de Bordeaux, 2025)
En tant qu’innovation majeure, la monnaie électronique s’est imposée dans l’écosystème financier en permettant aux agents économiques de répondre à des besoins distincts mais complémentaires tant en Europe qu’en Afrique. A cet effet, l’analyse de la monnaie électronique à l’aune de ces deux espaces géographiques, et précisément de trois espaces bancaires que sont l’UE, l’UMOA et la CEMAC, a notamment permis de mettre en lumière les différentes dynamiques qu’entraîne cet instrument moderne. En Europe, la monnaie électronique constitue une réponse pragmatique aux micropaiements dans une économie largement bancarisée. En Afrique, elle représente, bien plus qu’une simple solution aux micropaiements, un levier essentiel d'inclusion financière pour des populations majoritairement non bancarisées. Cette thèse propose une analyse juridique comparative de la monnaie électronique dans ces deux espaces géographiques, révélant des contextes socio-économiques contrastés ainsi que des perspectives radicalement différentes malgré une appréhension juridique commune. Afin de mener une analyse intégrant à la fois l’évolution juridique et technologique de la monnaie électronique et des moyens de paiements numériques, l’on consacrera la première partie de l’analyse à étudier les critères de qualification de la monnaie électronique, ce qui permettra de souligner que les espaces bancaires concernés par l’étude disposent d’une appréhension juridique commune en la matière, tout en ayant des appropriations technologiques différentes qui s’illustrent par des formes de monnaie électronique distinctes selon que l’on se trouve en Europe ou dans les espaces bancaires UMOA et CEMAC. Ensuite, l’analyse se poursuivra avec l’étude des innovations technologiques et des mutations juridiques qui ont eu lieu avec l’émergence de la monnaie électronique. Cette analyse sera également le pilier de la posture prospective dans laquelle s’inscrit cette thèse car elle permettra non seulement d’asseoir les réflexions sur la nécessaire évolution des critères monétaires face à l’émergence des moyens de paiements numériques, mais également de plaider pour un changement de paradigme qui consistera principalement à réduire l’ampleur du monopole monétaire traditionnel, et à instaurer une concurrence plus dynamique entre moyens de paiement. Dans cette démarche prospective ayant pour objectif d’améliorer l’efficacité des moyens de paiement et de garantir une inclusion financière plus optimale, l’on proposera également que soit attribué un cours légal à la monnaie électronique en Afrique, et que soit mis sur pied un jeton de monnaie électronique de banque centrale s’appuyant sur la technologie des registres distribués, et ce, afin de favoriser l’intégration économique africaine. En somme, la monnaie électronique constitue bien plus qu'une simple innovation technique. Elle est et peut devenir un véritable vecteur de transformation profonde des systèmes financiers et du droit monétaire. Son encadrement juridique doit donc continuer à évoluer pour accompagner son développement exponentiel. En Afrique particulièrement, les régulateurs gagneraient à en faire un instrument privilégié d'inclusion financière et d'intégration économique régionale, et ce, en optant pour des réformes juridiques et institutionnelles ambitieuses. Cette recherche propose ainsi de repenser les fondements du droit bancaire et monétaire non seulement afin d’adapter la monnaie électronique aux réalités d’une économie de plus en plus numérisée et moins centralisée, mais surtout afin de faire de cet instrument moderne un outil propice aux besoins d’intégration économique en Afrique. As a major innovation, electronic money has established itself in the financial ecosystem by enabling economic agents to meet distinct yet complementary needs in both Europe and Africa. To this end, the analysis of electronic money through the lens of these two geographical areas, and specifically of three banking zones – the EU, WAMU, and CEMAC – has notably highlighted the various dynamics generated by this modern instrument. In Europe, electronic money represents a pragmatic response to micropayments in a largely banked economy. In Africa, it constitutes far more than a simple solution for micropayments; it serves as an essential lever for financial inclusion among predominantly unbanked populations. This thesis offers a comparative legal analysis of electronic money in these two geographical areas, revealing contrasting socio-economic contexts as well as radically different perspectives despite a common legal understanding. In order to conduct an analysis that integrates both the legal and technological evolution of electronic money and digital payment methods, the first part of the analysis will be devoted to examining the qualification criteria for electronic money. This will underscore that the banking zones covered by the study share a common legal understanding of the matter, while having different technological appropriations that are illustrated by distinct forms of electronic money depending on whether one is in Europe or in the WAEMU and CEMAC banking zones. Subsequently, the analysis will continue with the study of technological innovations and legal transformations that have occurred with the emergence of electronic money. This analysis will also serve as the cornerstone of the forward-looking approach that underpins this thesis, as it will not only ground reflections on the necessary evolution of monetary criteria in the face of emerging digital payment methods, but will also advocate for a paradigm shift consisting primarily of reducing the scope of the traditional monetary monopoly and establishing more dynamic competition among payment methods. Within this forward-looking approach aimed at improving the efficiency of payment methods and ensuring more optimal financial inclusion, it will also be proposed that electronic money be granted legal tender status in Africa, and that a central bank electronic money token be established based on distributed ledger technology, in order to promote African economic integration. In sum, electronic money represents far more than a mere technical innovation. It is and can become a genuine vector for profound transformation of financial systems and monetary law. Its legal framework must therefore continue to evolve to support its exponential development. In Africa particularly, regulators would benefit from making it a privileged instrument for financial inclusion and regional economic integration, by opting for ambitious legal and institutional reforms. This research thus proposes to rethink the foundations of banking and monetary law not only to adapt electronic money to the realities of an increasingly digitized and less centralized economy, but especially to make this modern instrument a tool conducive to the needs of economic integration in Africa.
Keywords: Afrique; Bank; CEMAC; Communauté économique et monétaire en Afrique centrale; EU; Electronic money; Espace bancaire; Monnaie électonique; OHADA; Organisation pour l'harmonisation en Afrique du droit des affaires; Pays de l'Union européenne; UE; UMOA; Union économique et monétaire Ouest africaine; WAMU

An evaluation of China’s securitization regulatory system - Cao, Lei (Université de Montréal, 2025)
Since its innovation as a modern financial product in the 1970s, securitization has swept the global financial market. In 2000s, in order to ease China’s concentrated debt risks in the banking system and to improve the country’s imbalanced financial system, the Chinese government started to promote a trial program of securitization. An associated regulatory system was then created to facilitate the development of the Chinese securitization markets. Unlike regulations drafted and applied in North America, where an ex-ante regulatory analysis procedure and an ex-post evaluation system are installed, the current Chinese securitization regulation system is built mainly upon a basis of trial and interim rules. In other words, Chinese regulations regarding securitization were not comprehensively assessed before their adoption and there has been no systemic ex-post evaluation of the current securitization regulatory system in the past 20 years. This raises the question of whether the Chinese securitization regulation system facilitates the achievement of its regulatory objectives. The author purports to answer this question using three tools: The theory of regulation, legal historical analysis of law, and comparative law. To begin the analysis, the author designs an analytical framework based on the theory of regulation to evaluate Chinese regulations on securitization. In this evaluative framework, perspectives and criteria are stipulated to guide and draw the boundary of the evaluation. While applying the analytical framework, the author reviews the development of the Chinese securitization regulatory system over the past 20 years. The author studies the historical context of regulations established and regulatory modifications adopted in order to assess whether the logic embedded in the current Chinese securitization regulatory system is still valid. To better evaluate the Chinese securitization regulatory system, the author also applies a micro comparison of certain Chinese securitization regulations with their counterparts in North America. The purpose of this comparison is also to understand whether the Chinese characteristics in Chinese securitization regulations facilitate the achievement of its regulatory objectives. At the end of this assessment, the author provides a report to find the merits and disadvantages of Chinese securitization regulatory system. Due to the evaluative nature of this research, no demonstrated solutions are proposed in this report. Depuis sa création dans les années 1970, la titrisation s’est répandue à travers le marché financier mondial. Dans les années 2000, le gouvernement chinois a commencé à promouvoir le programme de titrisation afin d'atténuer les risques liés à la concentration de la dette dans le système bancaire et d'améliorer un système financier déséquilibré. La règlementation associée a été mise en place pour faciliter le développement du marché chinois de la titrisation. Contrairement aux régles créées et appliquées en Amérique du Nord, qui suivent une analyse ex ante —c’est-à-dire avant leur adoption — et une évaluation ex post — soit après leur application pendant une certaine période, le système de réglementation de la titrisation actuellement en vigueur en Chine a été élaboré sur la base d’essais et de mesures provisoires. Autrement dit, la Chine ne s’est pas fondée sur une analyse ex ante approfondie, et n’a mené aucune évaluation systémique ex post de ses réglementations de la titrisation au cours des vingt dernières années. Ce système chinois de réglementation de la titrisation facilite-t-il ou non la réalisation de ses objectifs réglementaires ? L'auteur tente de répondre à cette question à partir de trois outils : la théorie de la réglementation, l’analyse historique du droit et le droit comparé. Pour commencer, l’auteur conçoit un cadre analytique basé sur la théorie de la réglementation pour évaluer les dispositions chinoises en matière de titrisation. Dans ce cadre d’évaluation, des perspectives et des critères sont proposés pour guider et délimiter l’évaluation. À la lumière de ce cadre analytique, l’auteur replace la réglementation chinoise de la titrisation dans son contexte historique et retrace les modifications apportées au cours de deux dernières décennies. Il s’agit ainsi d’évaluer si la logique qui a présidé à l’adoption de ces règles reste valide dans le contexte actuel. Mais pour mieux saisir les caractéristiques de la réglementation chinoise de la titrisation, l’auteur ajoute à cette analyse historique interne à la Chine des micro-comparaisons de la titrisation chinoise et de ses règles avec leurs homologues nord-américains dans différentes sections de cette thèse. C’est ainsi qu’il sera possible de voir si les caractéristiques chinoises de la réglementation en matière de titrisation facilitent ou non la réalisation de ses objectifs. Au terme de cette recherche évaluative, l’on proposera un rapport qui mettra en lumière les avantages et les inconvénients du système chinois. En raison de sa nature évaluative, cette thèse ne proposera aucune solution aux inconvénients repérés.
Keywords: China; Chine; Evaluation of Chinese; Financial Regulation; Marchés chinois; Réglementation financière; Securitization; Securitization Markets; Securitization Regulation; Titrisation; Titrisation (réglementation)

La régularisation fiscale en France des avoirs étrangers non déclarés - Goudarzi, Laurent (Université Paris-Saclay, 2025)
La procédure de régularisation fiscale en France des avoir étrangers non déclarés témoigne du combat de l'administration fiscale contre l'omission des déclarations des comptes bancaires et autres actifs situés hors de l'État de résidence des contribuables.À grand renfort de moyens matériels et humains ainsi que d'un arsenal juridique efficaces assurant une synergie des autorités compétentes à déceler une telle fraude, la présente étude traite également des enjeux et autres failles gravitant autour de cette procédure de mise en conformité fiscale.Dans cette optique, il convient de s'intéresser aux causes de la fraude fiscale et la favorisant, de s'interroger sur la volonté persistante à vouloir dissimuler ses avoirs à l'administration fiscale et enfin, de démontrer en quoi les mécanismes instaurés de dissuasion contre une telle fraude tendent conformément aux valeurs démocratiques. The procedure for the tax regularization of undeclared foreign assets in France testifies to the tax authority its fight against the omission of declarations of bank accounts and other assets located outside the tax residence of taxpayers.With the help of material and human resources as well as an effective legal arsenal ensuring a synergy of the competent authorities to detect such fraud, the present study also deals with the issues and other loopholes revolving around this tax compliance procedure.With this in mind, it is necessary to look at the causes of tax fraud and encourage it, to question the persistent desire to hide one's assets from the tax authorities and finally, to demonstrate how the mechanisms put in place to deter such fraud tend in accordance with democratic values.
Keywords: Avoirs étrangers; Bank canvassing; Bank secrecy; Compliance; Compliance (droit); Démarchage bancaire; Foreign assets; Fraude fiscale; Lanceur d'alerte; Secret bancaire; Tax fraud; Whistleblower

Les partenariats entre fintechs et banques à l’ère de l’intelligence artificielle : enjeux stratégiques et défis juridiques en droit des affaires - Awanvoeke, Larios Borgia Dona (Université de Montréal, 2025)
Les partenariats entre fintechs et banques à l’ère de l’intelligence artificielle redéfinissent les modèles économiques et stratégiques du secteur financier. Face aux mutations technologiques, les banques traditionnelles s’associent aux fintechs pour innover, optimiser leurs services et répondre aux attentes des consommateurs. Toutefois, ces collaborations soulèvent des défis juridiques majeurs en matière de responsabilité, de protection des données et de conformité réglementaire. Ce mémoire analyse ces enjeux en adoptant une méthodologie combinant analyse doctrinale, droit comparé et étude des cadres réglementaires existants. L’approche doctrinale a permis d’explorer les concepts clés des fintechs, des banques et de l’IA, en mobilisant les théories économiques et juridiques pertinentes. L’étude comparative entre l’Union européenne, les États-Unis et le Canada a mis en lumière les différences réglementaires, notamment en matière de protection des données et de régulation de l’innovation. Enfin, l’examen des cadres législatifs actuels et des tendances émergentes, telles que les regulatory sandboxes et les innovation hubs, a permis d’anticiper les évolutions nécessaires pour encadrer ces transformations. Les résultats montrent que si l’IA favorise l’innovation et l’automatisation des services financiers, elle pose également des risques en matière de transparence des algorithmes, de cybersécurité et d’équilibre concurrentiel. L’étude met en évidence la nécessité d’une harmonisation réglementaire et de mécanismes de gouvernance adaptés pour garantir un développement équilibré du secteur. Ce mémoire propose plusieurs recommandations, notamment le renforcement des cadres juridiques sur la responsabilité algorithmique, la création de normes internationales harmonisées et la mise en place de collaborations entre banques, fintechs et régulateurs. Ces mesures visent à assurer un environnement financier sécurisé, innovant et conforme aux impératifs de transparence et de protection des utilisateurs. Ainsi, les partenariats fintechs-banques s’imposent comme un levier stratégique incontournable, nécessitant une régulation adaptée pour concilier innovation et stabilité du marché.
Keywords: Algorithm Transparency; Algorithmic Liability; Artificial Intelligence; Automation; Automatisation; Banks; Banques; Business law; Cadre réglementaire; Comparative Law; Competencia; Competition; Concurrence; Cybersecurity; Cybersécurité; Data Protection; Digital Transformation; Droit comparé; Droit des affaires; Financial Governance; Financial Innovation; Fintechs; Gestion des risques; Gouvernance financière; Innovation Hubs; Innovation financière; Innovation hubs; Inteligência artificial; Intelligence Artificielle; Intelligence artificielle; Partenariats stratégiques; Protection des données; Regulatory Framework; Regulatory Sandboxes; Responsabilité algorithmique; Risk Management; Régulation; Régulatory sandboxes; Strategic Partnerships; Transformation numérique; Transparence des algorithmes

L'obligation d'information du banquier : essai d'une théorie générale - Koyangana Mawoyi, Gracia (Université Paris-Saclay, 2025)
L'obligation d'information du banquier peine à trouver un cadre juridique cohérent. L'objectif principal de cette étude est de proposer l'essai d'une théorie générale de l'obligation d'information du banquier en abordant les questions qui dominent cette notion notamment les interrogations sur son contenu, sa nature et son régime. En effet, l'étude de la notion d'obligation d'information permet d'appréhender son contenu et sa nature marqués par un courant pluraliste qui tend à la multiplication des diligences d'information du banquier et donc à la multiplication des obligations d'information du banquier. Le contenu de l'obligation d'information du banquier va de l'information documentaire au conseil en passant par la mise en garde et l'éclairage selon le type d'opération envisagée et la qualité du bénéficiaire.Par ailleurs, la nature de l'exigence d'information du banquier traduit d'une part, une confusion entre les notions de devoir et d'obligation en droit positif alors qu'une distinction existe entre les deux notions conduisant en principe au régime de responsabilité contractuelle pour une obligation et au régime de responsabilité extracontractuelle pour un devoir. D'autre part, une imprécision peut être relevée concernant la nature extracontractuelle ou contractuelle de l'obligation d'information. Aussi, la pluralité de contenus et de natures de l'obligation d'information du banquier emporte des interrogations sur la cohérence de la notion.Cependant, cette pluralité témoigne de la volonté affichée de protection de la clientèle du banquier au regard de la fonction décisionnelle attachée à l'obligation d'information du banquier qui sert avant tout à contraindre le banquier à apporter des informations aux bénéficiaires, clients ou cautions, afin qu'ils puissent décider au mieux pour leurs intérêts. La recherche d'une cohérence du droit positif est également attendue par rapport au régime de l'obligation d'information du banquier.La controverse pendante ici tient à l'application de la responsabilité contractuelle à l'inexécution de l'obligation d'information du banquier même lorsque celle-ci est intervenue avant la signature du contrat. Cet état du droit positif est l'enjeux central qui fonde le raisonnement prônant la nature contractuelle de l'obligation d'information du banquier. Toutes ces considérations tendent à démontrer que l'obligation d'information du banquier est véritablement une notion fonctionnelle puisque la compréhension de la physionomie de l'obligation d'information se trouve dans la volonté du droit positif, notamment par l'action du juge, qui tend à apporter une solution aux difficultés concrètes rencontrées par les créanciers de l'obligation d'information.
Keywords: Bank; Banque (responsabilité); Divulgation d'informations; General theory; Information disclosure; Obligation d'information documentaire; Obligation d'éclairer; Obligation de conseil; Obligation de mise en garde; Obligation to advise; Obligation to enlight; Obligation to provide documentary information; Obligation to warn; Théorie générale

Etude comparative de la comptabilisation des stocks en PCGC et en SYSCOHADA - Kambale Kikono, Serge (International Journal of Innovation and Scientific Research, 2025)
Cet article a été consacré à une étude comparative de la comptabilisation des stocks en système comptable congolais et en Système comptable OHADA, avec comme finalité d’établir les points de convergence et de divergence entre ces deux systèmes comptables et dire si de ces deux systèmes comptables sont efficaces dans la comptabilisation des stocks. Ainsi, au terme de nos analyses, nous avons remarqué que les deux systèmes comptables comparés dégagent plus d’éléments de différence que de ressemblance en comptabilisation des stocks. Ces différences constituent, en effet des innovations majeures qu’apporte le Système comptable OHADA au Plan Comptable Général Congolais. D’autres avantages du Système Comptable OHADA sont également dus à des innovations intéressantes apportées par celui-ci en ce qui concerne certains aspects de la vie économique des entreprises. Parmi ces avantages, citons-en: la distinction des stocks, en particulier et la distinction les stocks en activités ordinaires et hors activités ordinaires, l’utilisation d’un compte de variation des stocks pour tout mouvement en rapport avec les stocks et la présence d’un compte pour enregistrer les services encours, etc. This article is devoted to a comparative study of stock accounting in the Congolese accounting system and in SYSCOHADA, with the aim of establishing the points of convergence and divergence between these two accounting systems and determining whether they are effective in stock accounting. At the end of our analysis, we have noted that the two accounting systems compared reveal more differences than similarities in inventory accounting. These differences are, in fact, innovations that SYSCOHADA brings to the PCGC. Other advantages of SYSCOHADA are also due to the major innovations it brings to certain aspects of the economic life of companies. Among these advantages are: the distinction between inventories, in particular, and liabilities and liabilities in general in ordinary and non-ordinary activities, the use of an inventory change account for any movement relating to inventories, the presence of an account to record services in progress, etc.
Keywords: Accounting; Comptabilité; Inventaire; Inventories

A framework for bank resolution in Namibia - Eiseb, Bryan Karl Gunther (University of Pretoria, 2025)
Banks are regarded as special financial institutions because, apart from the various critical intermediary and other functions they fulfil in a financial system, the hallmark of their business models is receiving deposits from the public and using such deposits for extending loans against interest from which they make profit. Unlike other companies, banks are however vulnerable to loss of public confidence and remain exposed to various risks and failure. Banks are thus critically important actors in domestic and global financial systems, - thus their safety is critical to the maintenance of financial stability. As a result, banks are subject to stringent regulation and supervision to ensure their safety. Despite prudential regulation, the failure of banks remains a reality. If the risk of bank failure is not adequately addressed through appropriate regulation and supervision, , it may result in a financial crisis like the 2008 Global Financial Crisis (2008 GFC). Because banks play a special role in an economy and their failure may have an adverse impact on financial stability and depositors, this thesis aligns with the view expressed by academics and international organisations that there is a need for a special regime (lex specialis) to deal with the failure of banks since normal insolvency procedures are not suitable for this purpose. f. This is because bank failures require swift, timely intervention by a supervisor to resolve failing banks in an orderly and optimal manner to ensure the maintenance of financial stability, depositor protection and relegating bailouts with taxpayers’ money as a last resort. A very notable lesson that emanated from the 2008 GFC is the criticality of special resolution frameworks for banks; the need to balance the interests of shareholders, creditors, and depositors, while promoting financial stability objectives. As a result, the need for special resolution frameworks for banks which empowers Resolution Authorities with adequate resolution tools and powers to resolve a failing bank timeous and orderly , has become a legislative imperative in contemporary financial systems. To deal with bank failures in Namibia, the Banking Institutions Act, 2 of 1998 (the BIA 1998) contained provisions that allowed for the assumption of control and liquidation of a failed bank. However, the newly enacted Banking Institution Act 13 of 2023 (the BIA 2023 which repealed the BIA 1998) has changed that position and introduced a single provision in section 70 that provides for bank resolution. Until now, prior to the introduction of this very new statutory provision, all bank failures in Namibia were dealt with under the limited supervisory tools of the BIA 1998. This study seeks to determine whether section 70 of the BIA 2023, is sufficiently aligned with international best practice as captured in the Financial Stability Board’s Key Attributes of Effective Resolution Regimes for Financial Institutions (FSB KAs), issued in 2011, as updated in 2014 and 2024. Alternatively, if the regime introduced by the BIA 2023 does not adequately align with the FSB KAs it is then considered whether the new Namibian bank resolution framework requires to be strengthened further to better align it with the FSB KAs. To consider possible further reforms to the new Namibian bank resolution regime, this thesis considers the resolution frameworks in Germany and Nigeria by way of comparative studies to observe best practices.
Keywords: Bank; Financial stability; Key Attributes; Namibia; Resolution

Problématique d’estimation de valeur actuelle des actifs dans l’espace OHADA - Baya Muzela, Jean Claude; Nyengele Mutambila, Moise; Nkongolo Kaajila, Dieudonné (Revue du contrôle, de la comptabilité et de l’audit, 2025)
Dans un contexte d’absence de procédure claire concernant l’estimation de valeur actuelle des actifs, l’étude a gravité autour de ce questionnement : « Comment estimer la valeur actuelle des actifs dans l’espace OHADA ? Quelles seront les implications de cette estimation sur le résultat des entités ?». Pour répondre à cette question, l’étude a opté la démarche déductive comme méthode de recherche. Elle est contextualisée et illustrée par des données empiriques issues d’un cas pratique enfin de renforcer l’applicabilité. L’objectif assigné consiste à présenter une possibilité aux organisations économiques d’estimer leur patrimoine actif en temps réel en tenant compte de leur contrainte spécifique à l’environnement OHADA. Enfin de mieux agencer la réflexion, trois grandes parties ont constitué l’ossature de cette étude. La première a reposé sur le modèle d’analyse, la deuxième sur le résultat et la discussion de la recherche et la troisième sur les limites de la recherche. Tout compte fait, le résultat de la recherche a révélé qu’il existe une relation inverse entre estimation de valeur actuelle et le résultat des entités. L’estimation entraine une diminution sensible du résultat du fait de la comptabilisation de dépréciations et de ce fait, les hypothèses empiriques émises ont été confirmées. A titre de recommandation, la transposition de la démarche proposée dans cet article est de strict conseil pour toute organisation qui se veut pérenne car, au-delà de l’amincissement du résultat, le maintien de la capacité d’autofinancement demeure une force pour l’entité.
Keywords: Actifs (valeur); OHADA

Impact of Blockchain Adoption, Regulatory Environment, and Institutional Investor Participation on FinTech Innovation - Almestarehi, Ahmad Abdel Rahim; Al-Ababneh, Hassan Ali; Malkaw, Eyad Mohammad (Theoretical and Practical Research in Economic Fields, 2025)
This study investigates how blockchain integration, regulatory policies, and the participation of institutional investors impact fintech innovation in Jordanian fintech companies. A descriptive analytical approach was used to evaluate and summarize the effects of these factors on innovation in the sector. An electronic survey was conducted among 125 administrative personnel working in Jordan's fintech industry. The results indicate a strong presence of blockchain adoption, involvement of institutional investors, and overall fintech innovation in these companies. However, the regulatory landscape in Jordan's fintech sector was found to be moderate. Furthermore, the analysis reveals that both blockchain integration and the regulatory framework significantly influence fintech innovation, with a significance level of 0.05. In light of these findings, the study suggests the creation of strategies to promote blockchain adoption, aiming to enhance efficiency and innovation in the industry.

Tax Reform and Investment Decision Effects in an Emerging Economy: Insights from Ghana - Yeboah, Michael; Danquah, Benjamin Adjei; Bawuah, Jonas; Nkwantabisa, Agyeiwaa Owusu (Theoretical and Practical Research in Economic Fields, 2025)
This study focuses on both domestic and foreign investment as indicators of economic growth in an emerging market context, examining the effects of tax reforms on investment decisions in Ghana from 1985 to 2020. The research employs a time-series analysis to integrate control variables like inflation, gross capital formation, and base rate, revealing their significant influence on investment activity in tandem with tax policy changes. Unlike previous research that mostly uses gross fixed capital formation as a proxy for investment, this study includes a wider range of investment types, giving a more complete picture of how the economy works. We did unit root and co-integration tests, which showed that the variables were first-order co-integrated. We performed the model estimate using a Vector Error Correction Model (VECM) and Granger causality tests. Results reveal that tax reforms have a measurable impact on investment patterns, underscoring the importance of adaptive tax policies in promoting sustainable economic development. The findings contribute to the broader literature on investment and fiscal policy in emerging economies, offering insights for policy-makers on optimizing tax strategies to encourage investment and drive economic growth.

A comparative statutory analysis of the causes of bank failures in Zimbabwe - Tsaura, Oscar (North-West University, 2025)
Zimbabwean financial sector has experienced significant periods of financial distress as depicted by numerous bank failures since 1980. Bank failure occurs when a financial institution experiences significant financial distress, rendering it incapable of fulfilling its obligations to depositors, shareholders and other stakeholders. In other words, bank failure is when a financial institution undergoes substantial financial distress rendering it unable to meet its obligations as they become due. In this thesis, the researcher adopted the definition of bank failure which refers to a situation where a bank is in financial distress and is recapitalised either by the central bank or a strategic investor, acquired by another institution, surrenders its license or the license is suspended, or it closes its operations altogether. This thesis reveals that in Zimbabwe bank failures can be attributed to various factors including the failure of regulatory and supervisory systems to detect irregularities in the operations of banking institutions. In addition, poor corporate governance practices such as inadequate oversight, inexperienced management, undue influence by dominant shareholders, nonperforming loans, excessive risk-taking, abusive related party transactions and noncompliance with laws are commonly cited as causes of bank failures in Zimbabwe. Bank failures often pose negative implications to the banking sector and banking stakeholders such as depositors and investors. This owes to the fact that banks serve as intermediaries that facilitate the avenues for deposits and extend credit services to individuals and the production sector of the economy. It is submitted that the proper functioning of banks requires effective and adequate regulatory supervision. Failure to provide robust and effective regulation of banks could lead to bank failures. This thesis presents a comparative analysis of the banking statutory framework of Zimbabwe and those of the UK and South Africa to determine if the banking laws in Zimbabwe are robust enough to prevent bank failures. The thesis reveals that the banking statutory framework in Zimbabwe is not robust enough to curb bank failures in times of stress because it lacks effective regulatory oversight. This thesis further reveals that poor banking regulation, inconsistent enforcement, weak regulatory insolvency procedures, and inadequate supervision framework are some of the weaknesses in the current banking statutory framework which needs to be rectified in order to combat bank failures effectively in Zimbabwe. The Banking Act does not fully incorporate the international best standards on bank supervision to prevent bank failures. Consequently, the banking statutory framework in Zimbabwe does not comprehensively and effectively provide for the prevention of bank failures like those of the UK and South Africa. The robustness of the banking statutory framework is in providing adequate and effective regulatory provisions and enforcement mechanisms that curb bank failures in Zimbabwe. The researcher proposes the adoption of a new model, the Zimbabwean twin peaks model, comprising the Zimbabwean Prudential Regulatory Authority and the Zimbabwean Financial Sector Conduct Authority. It is argued that if the adoption of the twin peaks model is considered and robustly implemented, it can prevent the causes of bank failures in Zimbabwe.
Keywords: Bank failure; Banking legislation; Banking statutory framework; Banks; Curatorship; Financial regulations; Financial stability; Fraud; Money laundering; Political instability; Zimbabwe

The Protection of E-Banking Services Against Cybercrimes in Cameroon: Prospects and Challenges - Ghaseh, Nkambeh Allen (International Multilingual Journal of Science and Technology, 2025)
This article seeks to examine the extent to which users of e-banking services are protected in Cameroon. Over the past decades financial transactions have gradually emerged from traditional methods to modern forms of banking. The Information and Communication Technology (ICT) has transformed the banking system into a digital arena. With e-banking, customers can access their bank accounts, transfer funds, pay bills, and check their accounts balances. Banks serve as the backbone of every modern economy and should be protected. The development of e-banking in the 1980s with the aid of ICT has rendered banks and their customers vulnerable to cybercrimes. As an effort to combat cybercrimes and ensure cyber security in Cameroon, the 2010 Cyber Law provides both substantive and procedural rules. It is rather unfortunate that, the measures put in place to ensure cyber security and protect bank customers against cybercrimes are to a greater extent ineffective. The main objective of this article is to determine the protection accorded to banks and their customers against cybercrimes. The method adopted in the course of this work is doctrinal wherein, both primary and secondary sources of data were collected. The findings reveal among others that, the measures put in place to combat cybercrimes within the banking sphere in Cameroon are not effective. There is lack of explicit definitions for cyber offences. Most of the offences provided by the 2010 Cyber Law are vague and ambiguous. We therefore recommend that, the 2010 Cyber Law should be amended to address the current issues of ICT. This amendment should include explicit definitions for the different forms of cybercrimes with severe sanctions. Banks are advised to put in place effective monitoring machineries to mitigate cybercrimes.

The regulation of crypto-assets in South Africa with particular regard to crypto-asset market manipulation - Mgijima, Lwandiso (University of Pretoria, 2025)
Market manipulation is one of the dishonest means used by unscrupulous investors to make unjustified profits. It is conduct which unlawfully interferes with the normal operations of the markets in order to create false appearances with respect to the trading activity or the price of a financial asset. Market abuse is one of the various challenges plaguing the crypto-assets market, and is one of the financial regulators’ priority concerns. This study examines and discusses the problem of market manipulation in crypto-assets, and the need for the enactment of an effective regulatory framework in order to combat this problem and to promote investor protection and safeguard the integrity of the markets. The study finds that South Africa and other countries need to introduce rules in crypto-assets market which aim at regulating the activities of crypto-asset service providers. Currently South Africa has not enacted a comprehensive regulatory framework to address the various illegal uses of crypto-assets. The general approach adopted by South Africa to regulate crypto-assets activities involves subjecting crypto-asset service providers and their activities under the various financial sector laws established to regulate the traditional financial markets. This approach has been criticised as being inefficient in light of the unique risks presented by crypto-assets. The study discusses some of these arguments in detail and concludes by highlighting the need for the adoption of innovative regulations, in the long term, which comprehensively and effectively addressed the various risks presented by crypto-assets which also include market manipulation.
Keywords: Crypto-asset; Crypto-assets; Framework; Manipulation; Markets; Misconduct; Regulation; Service provider

Essays on banking and society - Heyert, Axelle (Université de Strasbourg, 2025)
This dissertation examines the relationship between banking and society. It contributes to a better understanding of how banking affects society and, in turn on how society shapes banking practices. The first chapter studies the impact of inflation on trust in banks. Chapter two deals with the effect of trust in banks on financial inclusion. The third chapter investigates whether financial inclusion influences life satisfaction. Chapter four delves into how female bank leadership affects firm credit. The final chapter focuses on the influence of bank leaders’ age on sustainable lending. Overall, this dissertation highlights the important role of banks in societal development and the major influence of society in shaping banking practices.
Keywords: ACCESS TO CREDIT; Accès au crédit; Banking; Banks; Banques; Bonheur; Confiance; Financial inclusion; Gender; Genre; Inclusion financière; Inflation; Life satisfaction; Prêts durables; Sustainable lending; Trust in banks

Financial regulation and risk management: addressing risk challenges in a changing financial environment - Ojo, Marianne (Munich Personal RePEc Archive, 2025)
Will the April 2nd Announcement generate its intended objectives? It’s still early days – however, it appears increasingly likely that negotiation outcomes – particularly between those significantly impacted by the Announcement, will be a major determinant in deciding whether the tariff hikes resulting from the April 2nd Announcement, will be short or long term. As of the 11th April, 2025, President Trump’s universal tariffs on China had amounted to 145% whilst China announced tariffs of 125% on U.S imports. Amongst other things, this paper aims to address complexities and challenges faced by regulators in identifying and assessing risk, problems arising from different perceptions of risk, and solutions aimed at countering problems of risk regulation. It will approach these issues through an assessment of explanations put forward to justify the growing importance of risks, well known risk theories such as cultural theory, risk society theory and governmentality theory. In addressing the problems posed as a result of the difficulty in quantifying risks, it will consider a means whereby risks can be quantified reasonably without the consequential effects which result from the dual nature of risk that is, risks emanating from the management of institutional risks.
Keywords: Financial Forecasting and Simulation; General Financial Markets; International Financial Markets; Regulation and Business Law

A trans-border African crypto asset licence to promote economic growth and deepen financial inclusion - Van der Lith, Johann Daniel (University of Pretoria, 2025)
Financial technology (Fintech) is a rapidly growing industry, both locally and globally. In various ways, Fintech is undeniably transforming financial services and products in every possible part of the financial sector by changing how people access and use financial services. By using innovative technologies, such as distributed ledger technology and cloud technology, and combining large data sets, including alternative data sets, better products can be provided that can be hyper-personalised for market segments and improve access and participation in respect of financial services. Fintech is solving issues that touch the consumer, through a bottom-up approach, considering the retail consumer as a starting point, in contrast to the common traditional finance evolution from the institutional investors to the retail consumer in a top-to-bottom approach. What is exciting about what Fintech can do for Africa, is that it can move inefficiencies in services and product life cycles to become efficiencies and move the frontiers for already efficient products and services. Fintech, therefore, provides an opportunity to improve the archaic and pave the way for the future. This study focuses mainly on crypto assets to limit its scope. It first examines the Fintech landscape in Africa, more specifically, the activity level in each selected comparative country, namely Mauritius, Kenya, Zambia, Namibia and South Africa, and how the activity benefits or can potentially benefit the economy in the host country and lead to the deepening of financial inclusion. It further examines the regulatory frameworks in those countries. The study examines the regulatory approach taken and the local activity, exploring some of the risks identified in each country, and considers the requirements that regulators chose to implement to mitigate these risks, as well as the current state of regulatory frameworks. Consideration is given as to whether similarities in both the risks and the mitigation requirements exist and how this can be aligned across jurisdictions. Recently, international standard-setting bodies have increased their focus on ensuring the alignment and cooperation of regulatory approaches globally. In light of the call for alignment and increased collaboration through policy recommendations and guidance, and or regulators to provide comprehensive and effective regulatory approaches without stifling innovation, this study considers the theoretical possibility of allowing certain Fintech companies, specifically crypto asset service providers (subject to specified conditions) to operate across jurisdictions with a trans-border licence. This study examines Europe’s Markets in Crypto Assets Regulation, as it was the first of its kind continental-wide framework for crypto assets, offering numerous lessons to be learned from this framework. The Commonwealth Model Law on Virtual Assets is also considered, as it is intended to assist member countries in implementing Virtual Asset and Virtual Asset Service Provider regimes in their respective jurisdictions, as they deem appropriate. Lastly, the study will explore what a theoretical trans-border regulatory framework containing prudential and market conduct requirements could look like and what embedded supervision tools, for instance, through forensic nodes or zero-knowledge proofs, could be utilised to ensure that all the regulators participating as part of a licencing panel receive real-time data and have a full view of the level of compliance with the requirements imposed by the joint framework and can proactively and intrusively act, when needed. The proposed trans-border regulatory framework aims to support crypto asset service providers with multi-jurisdictional strategies in Africa in scaling their operations, with a focus on building Africa as a global Fintech hub. The proposed framework aims to achieve this through a harmonised regulatory framework that simplifies compliance, increases efficiencies, enhances innovation, allows for scalability, and better risk management. In addition to the goal of positioning Africa as a globally recognised Fintech hub, the harmonised framework aims to realise the purported benefits of the technologies utilised by crypto asset service providers, thereby deepening financial inclusion and promoting inclusive economic growth through increased access and participation, as well as lower costs.
Keywords: Crypto assets; Embedded supervision; Financial inclusion; Financial technology; Regulatory frameworks

Artificial Intelligence in Accounting: Revolutionizing Financial Management in the Digital Landscape - Alnaimat, Mohammad Ahmad; Korsun, Inna; Lutsenko, Kostiantyn; Khodorkovskyi, Oleksandr; Artemchuk, Mykyta (Theoretical and Practical Research in Economic Fields, 2025)
The use of artificial intelligence (AI) builds up the accounting system efficiency, increases data entry accuracy and simplifying the accounting process. The aim of the study is to prove the effectiveness of modern AI-based information technologies (IT) in accounting and the possibilities of AI application for process optimization. The effectiveness and efficiency were proven using comparison methods, statistical analysis, graphical cause-and-effect analysis, modelling using the linear regression method. The assessment was carried out using quantitative and qualitative indicators of labour productivity and process optimization. The results of the study showed that 18 accounting department employees on average are needed to perform standard transactions in the companies studied without AI. With AI, 1 person can handle such a volume of work. Accordingly, with the implementation of AI, the average reduction in Transaction Processing Time per Week is 696.26 hours. Regression analysis confirmed that the implementation of AI increases the companies’ productivity in terms of Transaction Processing Time. Reducing the Data Processing Complexity by one unit leads to a reduction in transaction processing time by 592.69 seconds. Each percent increase in Data Entry Accuracy contributes to a reduction in processing time by 5135.51 seconds. The prospects for implementing AI in accounting include further improving algorithms to increase the accuracy and speed of transaction processing, optimizing material and time consumed.
Keywords: Accounting; Artificial Intelligence; Automation; Data analytics; Digital environment; Financial management; Inteligência artificial; Intelligence Artificielle; Machine learning

Le régime fiscal de la TVA à l’épreuve des activités numériques au Mali - Daou, Yacouba; Camara, Oumar Sinè; Toe, Souleymane (Revue africaine de droit des affaires, 2025)
Le commerce électronique au Mali connaît une forte croissance, mais l’inadaptation du régime fiscal, notamment en matière de TVA, engendre d’importantes difficultés. La nature immatérielle et extraterritoriale des transactions numériques complique leur contrôle, favorisant ainsi l’évasion fiscale et la fraude. De plus, l’identification des acteurs du commerce numérique reste un défi majeur, rendant l’application de la législation fiscale inefficace. Pour y remédier, une réforme s’impose particulièrement par la mise en place d’un mécanisme de collecte de la TVA par les plateformes en ligne, comme l’ont fait le Kenya et le Nigeria. Cette mesure permettrait de mieux encadrer la fiscalité du commerce électronique, d’assurer une concurrence équitable et d’optimiser la mobilisation des recettes fiscales.

Money Laundering: New Technologies and Control Challenges (Cryptocurrencies, Blockchain) - Kontogeorgis, Georgios (International Multilingual Journal of Science and Technology, 2025)
Tackling corruption is a global issue and tackling it effectively requires determination, cooperation and specialised technological knowledge. A significant proportion of global GDP is the sum of the money associated with corruption and fraud. The main objective of this article is to assess how new technologies such as cryptocurrencies and blockchain can combat corruption. The methodology of this article is a literature review. Specifically, scientific articles from databases and international organizations with expertise in new technologies are studied. This article deals with the new ways of corruption and money laundering. New technologies and the knowledge of them are a very important element in order to deal effectively with corruption. Perpetrators of financial crimes are usually ahead of the auditing authorities in terms of techniques and therefore knowledge of the new technology and the possibilities it offers is essential to effectively combat corruption and fraud globally. Cryptocurrencies and blockchain can combat corruption primarily due to their key characteristics of transparency, security, and decentralization. A key prerequisite for the transparency of cryptocurrencies is the application of supervision rules by the responsible authorities and the implementation of blockchain technology. In practice this is often not the case and cryptocurrencies are used as a money laundering tool.
Keywords: Corruption; Cryptocurrencies; Fraud; Money laundering; New technologies

La responsabilité civile des experts-comptables dans le droit de l’OHADA - Ngue, Elise Rolline (Revue africaine de droit des affaires, 2025)
Dans le cadre de l'OHADA, la responsabilité civile des experts-comptables vise à protéger les parties prenantes tout en assurant la sécurité juridique de la profession. Le cadre juridique repose principalement sur l'Acte uniforme portant sur le droit comptable et à l'information financière (AUDCIF), sur l'Acte uniforme relatif au droit commercial général (AUDCG) et sur l'Acte uniforme relatif au droit des sociétés commerciales et du groupement d'intérêt économique (AUSCGIE). Ces textes établissent les fondements de la responsabilité des experts-comptables vis-à-vis des clients et des tiers. La responsabilité civile de l'expert-comptable dans l’espace OHADA est régie par une obligation de moyens. Cela signifie que, bien que l'expert-comptable soit tenu d'utiliser toutes ses compétences pour fournir un service conforme aux règles comptables et juridiques, il n'est pas tenu à une obligation de résultat, sauf dans des cas spécifiques. De plus, il peut être tenu responsable vis-à-vis des tiers lorsqu'une faute commise dans l'exercice de ses fonctions leur cause un préjudice direct. Cependant, des limites existent dans la régulation actuelle, notamment en ce qui concerne la protection des tiers et la question des délais de prescription. En parallèle, des mécanismes de protection sont mis en place pour sécuriser la pratique professionnelle de l'expert-comptable. Ces protections incluent les clauses limitatives de responsabilité, les causes d’exonération (comme la force majeure ou la faute du client), ainsi que des assurances professionnelles couvrant les risques liés à la responsabilité civile. Les ordres professionnels jouent également un rôle clé en encadrant la déontologie et la discipline des experts-comptables, apportant une garantie supplémentaire aux clients et une certaine immunité disciplinaire aux experts-comptables en cas de faute mineure. Enfin, des perspectives d'amélioration du cadre juridique sont nécessaires pour renforcer l’équilibre entre la protection des parties prenantes et la sécurité juridique des professionnels. Cela inclut une réforme visant à clarifier certaines dispositions légales et à encourager une répartition plus juste des risques entre experts-comptables, clients et tiers.

Effects of Dynamic Capabilities and Multichannel Integration Quality on Bank Performance; A Moderated Role of Environmental Dynamism : A Moderated Mediation Model Analysis - Geleta, Negash; Amentie, Chalchissa; Getahun, Misganu (African Journal of Economic and Business Research, 2025)
This study investigates the effects of dynamic capabilities (DCs) and multichannel integration quality (MCIQ) on the performance of banks (BP). It also explores the moderating role of environmental dynamism in the banking industry, using a moderated mediation model. Quantitative analyses were employed to examine data collected from multiple banks. Structural equation modeling (SEM) was used to test the relationships between variables, while moderation and mediation effects were analyzed using SEM-AMOS. The findings reveal that dynamic capabilities and MCIQ significantly enhance bank performance. Furthermore, environmental dynamism (ED) moderates the relationship between these variables, intensifying their effects on performance under high levels of dynamism. The mediation analysis shows that MCIQ partially mediates the impact of dynamic capabilities on bank performance. The study is limited by its cross-sectional design, which restricts causal inferences. Additionally, the findings may not be generalizable to non-banking industries or regions with distinct regulatory frameworks. The results provide actionable insights for bank managers, emphasizing the importance of fostering DCs and enhancing MCIQ to sustain performance in rapidly changing environments. The findings highlight significant social benefits, as improved dynamic capabilities (DCs) and critical information quality (MCIQ) enhance bank performance, fostering economic stability, financial inclusion, and customer trust. By enabling resilience and innovation in dynamic environments, banks contribute to broader societal goals, including sustainable development and socio-economic growth. This research contributes to the literature by integrating DCs and MCIQ in a moderated mediation framework, offering a novel perspective on their interplay with environmental dynamism in the banking sector.
Keywords: Dynamic Capabilities; Environmental Dynamism; Moderated Mediation Model; Multichannel integration quality

An analysis of the challenges in combatting money laundering within Bureaux de Change establishments in Botswana - Mokone, Philadelphia Pontsho (Journal of Money Laundering Control, 2025)
PURPOSE : Financial institutions such as Bureaux de Change are susceptible to money laundering, posing a significant risk to a nation’s financial stability and security if not properly regulated and supervised. Botswana is a member of the Financial Action Task Force (FATF), a global organisation that sets standards, promotes policies to prevent money laundering, terrorist financing and arms proliferation, all to safeguard the global financial system. Efforts have been made to incorporate FATF recommendations on money laundering into the fiscal laws of Botswana. However, some deficiencies still remain. Although there are no recorded cases of money laundering in Botswana, Bureaux de Change entities are susceptible to it as their business involves cash transactions and rapid money transactions. This paper aims to analyse the challenges faced by Bureaux de Change entities in combating money laundering in Botswana. This will be done by assessing the effectiveness of the current regulatory framework and role of the regulatory authorities in combating money laundering within Bureaux de Change entities. DESIGN/METHODOLOGY/APPROACH : This paper provides a comprehensive examination of the obstacles faced by Bureaux de Change entities in Botswana when it comes to combating money laundering. A qualitative research method and doctrinal research method are both used in this context. FINDINGS : It is hoped that policymakers and other relevant persons will adopt the recommendations provided in the paper to enhance the curbing of money laundering in Botswana. RESEARCH LIMITATIONS/IMPLICATIONS : This paper is only limited to the regulation of money laundering within the Bureaux de Change entities in Botswana and does not provide empirical research. PRACTICAL IMPLICATIONS : This paper is useful to policymakers, lawyers, law students and regulatory bodies especially in Botswana. SOCIAL IMPLICATIONS : This paper suggests changes to the Bank of Botswana (Bureaux de Change) Regulations of 2004 to improve their effectiveness, robustness and competitiveness in combating money laundering. ORIGINALITY/VALUE : This paper is original research on the challenges of combating money laundering within Bureaux de Change entities in Botswana.
Keywords: Botswana; Bureaux de Change; Cash transactions; Financial security; Financial stability; Money laundering; Risk; Supervision

Les principes comptables de l’OHADA à l’ère de la comptabilité informatisée - Tankoano, Gnoari (Revue africaine de droit des affaires, 2025)
Dans un environnement des affaires marqué par l’omniprésence des technologies de l’information et de communication, le législateur OHADA a fait l’option de renforcer et de moderniser son arsenal juridique face aux défis posés par l’usage des outils numériques dans la pratique comptable. En effet, certes, les principes classiques régissant l’élaboration, la tenue et la sécurité des comptes ainsi que les comportements des comptables restent d’application. Du reste, l’étude a dédié à ces principes des analyses appréciables. Cependant, les nouvelles règles permettent de hisser ces principes classiques à la hauteur des défis de la digitalisation de l’activité comptable. Elles concourent à l’impératif de fiabilité, de sécurité, d’authenticité et d’intégrité de l’information comptable, face aux risques d’altération aisée, de fugacité, de surpression et de modification d’une information automatisée. Toutefois, la couverture du droit OHADA à cette nouvelle réalité n’est que partielle et ne parait pas approfondie. Pour une matière qui fait rarement l’objet d’études approfondies par les juristes, notre article, tout en révélant les innovations et les défis, jette les bases de réflexions. Cet exercice est essentiel au regard de la double technicité du sujet abordé, tenant, d’une part, à son objet, à savoir la comptabilité, et d’autre part, à la prise en compte des technologies de l’information et de la communication. En effet, non seulement, l’étude permet aux entités et praticiens d’avoir une meilleure compréhension des principes comptables modernes, mais aussi, elle offre aux contrôleurs des outils d’analyse de la conformité, et aux juges une compréhension et interprétation plus éclairées de cette discipline singulière. Les propositions qui en ressortent permettront au législateur de combler les incohérences et insuffisances juridiques afin de répondre plus efficacement aux défis de la digitalisation de la comptabilité.

The effects of Basel III on the intermediation and market activities of WAEMU banks - Kouakou, Thiédjé Gaudens-Omer (University Library of Munich, Germany, 2025)
This paper analyzes the effect of Basel III adapted to WAEMU on the behavior of banks in the zone (intermediation and market activities). After having developed a model for optimizing the return on bank equity, under various constraints (balance sheet constraints, Basel III regulatory constraints), we resort to linear programming via the Danzig simplex algorithm and to a structure of reasonable rates to obtain the optimal values of the various bank balance sheet items. The results, obtained by comparing these theoretical values with the values observed before Basel III (before January 1, 2018), show an increase in the supply of loans, obtained not only from deposits and bank refinancing but also via resources from the financial markets. We can also observe the intuitive result of an increase of bank reserves in line with the constraint that Basel III imposes on banks to increase their liquidity. In short, Basel III tends to strengthen bank financing in the zone, while improving the soundness of banks through the constitution of larger reserves.
Keywords: Calibration; Credit supply; Linear programming; Prudential regulation

L’enrichissement sans cause des établissements de crédit dans le droit de la Communauté Economique et Monétaire de l’Afrique Centrale (CEMAC) - Nfoutcha, Georges (Revue Africaine des Sciences Juridiques, Administratives et Politiques, 2025)
Il ne devrait guère résister de contradiction entre l’enrichissement sans cause et l’enrichissement illicite des établissements de crédit. Le premier relève du Droit civil alors que le second relève indubitablement du Droit pénal. Cette distinction devrait s’estomper en pénalisant l’enrichissement sans cause des établissements bancaires. En ce sens, l’infraction d’enrichissement sans cause des établissements permettrait de renforcer la politique pénale ou criminelle. L’enrichissement sans cause des établissements de crédit, ou l’enrichissement injustifié en Droit français, pose également la difficulté de la justice sociale. La question de la répétition de l’indu semble déjà réglée sous l’emprise de la législation en la matière. Mais, le souci de l’indemnisation mériterait d’être réglementé avec beaucoup d’acuité. Pris à ce titre, la mise en cause de l’enrichissement sans cause, fut-il un établissement de crédit, nécessiterait autant de restituer ce qui est dû, mais également indemniser la victime. Cette mesure devrait s’opérer de la manière la plus juste dans la mesure du possible. Les exigences d’équité y primeraient. Le droit de la Communauté Economique et Monétaire de l’Afrique Centrale gagnerait à se doter d’un véritable fond des dépôts de risques de l’enrichissement sans cause. Cette institution viserait à recevoir ces deniers en toutes fins utiles. Aussi, l’article 1303 du Code civil français résultant de l’ordonnance du 10 février 2016 devrait nourrir notre arsenal juridique sur la mise en œuvre d’une notion d’origine jurisprudentielle en quête de consistance digeste.
Keywords: Civil right; Credit institutions; Criminal law; Criminal policy; Droit civil; Droit pénal; Enrichissement illicite; Enrichissement sans cause; Etablissement de crédit; Illicit enrichment; Institution; Penal policy; Politique criminelle; Politique pénale; Unjust enrichment

Essai sur l'optimisation fiscale : exploration des mécanismes d'optimisation fiscale à travers l'étude des groupes de sociétés - Bakhtous, Siham (Université de Perpignan Via Domitia, 2025)
Cette étude explore les contours et les tensions de l'optimisation fiscale dans un monde globalisé et numérisé, à travers le prisme des groupes de sociétés. En retraçant l'histoire de l'impôt, elle met en lumière les transformations profondes du système fiscal mondial, où les stratégies fiscales transfrontalières se sont progressivement développées, en dehors des prévisions des législations nationales. Bien qu'enraciné dans le principe fondamental de la liberté de choisir la voie fiscale la moins imposée, l'optimisation fiscale a évolué en réponse aux mutations économiques, juridiques et technologiques, donnant lieu à des pratiques parfois controversées qui se situent aux frontières de la légalité et de l'éthique. À l'intersection du droit, de l'économie et de la politique fiscale, l'optimisation fiscale dépasse le simple objectif de réduction de la charge fiscale : elle reflète un processus global où la mobilité des capitaux et des actifs immatériels perturbe les règles fiscales classiques. Bien que souvent conformes à la législation, ces pratiques d'optimisation fiscale dites « agressives » perturbent l'équilibre des systèmes fiscaux mondiaux, contribuant à un phénomène préoccupant : l'érosion de la base d'imposition et le transfert de bénéfices vers des juridictions à faible fiscalité. Cette dérive a mis en évidence les défaillances des systèmes fiscaux nationaux, incapables de suivre le rythme des mutations économiques et de réguler efficacement les pratiques des multinationales. En déconstruisant les mécanismes sous-jacents de l'optimisation fiscale agressive, cette recherche invite à une critique constructive de l'arsenal législatif actuel. Elle souligne l'urgence de repenser les instruments fiscaux dans un contexte où la mobilité du capital et des actifs immatériels redéfinit les règles du jeu économique et de restaurer un équilibre entre les exigences d'efficacité économique des multinationales et la nécessité de garantir une justice fiscale à la hauteur des enjeux mondiaux
Keywords: Base erosion; Digital; Droit fiscal (droit international); Déductions fiscales; Groupes de sociétés; Impôts; Numérique; Optimisation; Optimization; Profit shifting; Restructuration; Restructuring; Réductions fiscales; Tax; Transfert des bénéfices; Érosion de la base d'imposition; Évasion fiscale

The Artificial Intelligence (AI) framework and the benefits of its use in internal audit - Kontogeorgis, Georgios (International Multilingual Journal of Science and Technology, 2025)
AI is well known today as a valuable tool that can improve our daily lives. In addition, it can improve the efficiency and productivity of many professions, such as the internal auditor. The research methodology is literature review. The primary objectives of the article are twofold: Firstly, to provide a comprehensive description of the institutional framework for the operation of AI internationally, and secondly, to examine the benefits that arise from the use of AI in internal audit units and organisations in general. The significance of the research lies in its examination of artificial intelligence (AI) as a valuable instrument in the arsenal of internal auditors. The findings suggest that AI has the potential to enhance the efficacy of internal audits, reduce the time required for their execution, reduce the frequency of internal audits, and, in general, optimise the operations of companies and organisations.
Keywords: AI; Artificial Intelligence; Corruption; Fraud; Inteligência artificial; Intelligence Artificielle; Internal audit; Management

Impact of the basel accords on small indigenous banks in developing countries : the case of Zambia - Rolls II, Douglas Walter (University of Pretoria, 2025)
The purpose of this thesis is to evaluate the impact of the Basel Accords on small indigenous banks in developing countries, with particular concentration on small Zambian banks. The problem statement intends to investigate whether implementing the three Basel Accords is conducive to the growth of small banks in Zambia. The study further aims to determine whether the present approach to legal regulation of small banks in Zambia is appropriate. The methodology is based on desk-bound research and examination of both primary sources and secondary sources of material such as books, journals, and relevant articles. The study is impacted by the dearth of secondary research work and the difficulty of getting information from sources like the Zambian central bank and other information centres. While Basel I and II seem to have stabilised the Zambian financial sector, the Basel III Accord appears to have impacted negatively on many small banks to the extent that they have been forced into merger and acquisition arrangements with larger foreign banks to fund their undercapitalised positions to survive. It also emerges that the Zambian financial system is strongly linked to the international global economy; regionalisation with organisations like SADC and COMESA being the first stages in the process. This situation is likely to introduce increased instability in the Zambian financial sector by making banks more vulnerable to the vagaries of the international financial markets. It is thus recommended that the Zambian central bank should be more proactive in lobbying for better conditions for small banks from the Basel Committee for Banking Supervision and other international financial regulatory bodies; it should also avoid “cutting and pasting” rules from other jurisdictions to avoid possible distortions in the banking sector. It should also encourage further development of primary and secondary markets in low-cost paper and provide small banks with long-term, low-interest loans to support their growth. The Bank of Zambia, the Zambian central bank, should consider establishing a separate Act financial services Act for small banks to better regulate them. The central bank should also seek out non-Basel Accord solutions for small banks including re-examining the positive aspects of the infant-industry argument. Lastly, it should introduce a formal system for classifying banks in Zambia. At the international level, it is suggested that the global standard-setting bodies should undergo radical reforms to ensure that they are in tandem with the problems that banks in developing countries face as well as allow them to have a say in global standard setting. It is recommended that global standard-setting bodies apply simpler rules for smaller banks. The impact of the Basel Accords on small indigenous banks in developing countries and Zambia, in particular, is important because of the role that small banks play in developing economies in growing small and medium-sized businesses that are often ignored by large foreign banks. It is also important that small banks are allowed to grow into large and medium-sized banks to effectively compete against foreign multinational banks. Institutions based on neoliberal ideals appear to only serve Western businesses’ interests despite their call for all countries to create a level playing field. Due to the dearth of empirical research, there are several gaps in the work that may provide opportunities for further research in this important area of the law.
Keywords: Banking supervision; Basel accords; Basel committee; Developing countries; Financial regulatory framework; Small banks